Perkawinan Anak di Bawah Umur dalam Perspektif Hukum Islam - Yusuf Hanafi (Ulumuna, 2008)
Under age marriage is not a new case in Indonesia. This practice has been performed by many people either in villages or big cities for a long time. Its causes are diverse from economic factors, poor education, to superficial understanding of cultural and religious values. In addition to causing social, psychological and health problems, under age marriage brings about legal problems. For example, Syekh Puji and Ulfa’s marriage opens controversy areas between traditional, Islamic, national and international laws because each has different juridical perspectives. This fact causes at least two legal problems: first, harmony between one law and another; second, challenges for marital legislation in term of under age marriage. This writing is aimed to show the urgency of marital law review to answer legislative challenges toward Islamic law harmony with globalization era today.